Building A New Academic Field: The Institutionalisation Of Taiwan Studies In Europe - Ohlendorf, Hardina (Penerbit Universiti Sains Malaysia (USM Press), 2017)
The emergence of Taiwan Studies as a new area study in Europe is an intriguing phenomenon. It started more or less "from scratch" at a time when the area studies model was seriously challenged in academic debates. Since then the feld has rapidly expanded in Europe. This paper seeks to analyse the factors that have facilitated the successful institutionalisation of academic Taiwan Studies in a region that otherwise does not have close relations with Taiwan. It argues that fnancial overtures from Taiwan have found fertile ground in Europe, which has to do with the distinct Asian Studies tradition on the continent, a major restructuring of the university feld since the 1990s, and the specifc historical circumstances of Taiwan's political and social transformation in the late 20th and early 21st century. While these wider developments have provided advantageous circumstances, the successful construction and institutionalisation of a new thriving academic feld can only be explained by the strong personal commitment of key Taiwan scholars in Europe and the skilful integration of individual eﬀorts through the creation of a Europe wide network.